Medical versus Surgical Patients with Clostridium difficile Infection: Is There Any Difference?. Issue 12 (December 2016) - Silva-Velazco, Jorge; Hull, Tracy L.; Messick, Craig; Church, James M.
Severity of Clostridium difficile infection (CDI) varies from one patient to another. We aimed to test the hypothesis that surgical patients would suffer more severe CDIs than medical patients. Patients receiving in-hospital medical or surgical treatment for any underlying disease from 2007 to 2012, who developed CDI, were divided into two groups: "Medical group" and "Surgical group." Demographics, disease characteristics, and outcomes including mortality and recurrence were compared. Of 3231 patients with CDI evaluated, 1984 (61.4%) and 1247 (38.6%) were medical and surgical patients, respectively. Surgical patients had more severe CDIs than medical. However, the long-term effects of CDI were worse in medical patients, with more and quicker deaths. Recurrence was comparable between groups. Surgical patients were more frequently male, older, and obese; had higher white blood cells but lower levels of hemoglobin, hematocrit, and prealbumin; and had a higher rate of severe CDI. Conversely, medical patients had fewer in-hospital days, CDI appeared earlier, and had greater 30-day mortality and total number of deaths, with death after CDI occurring earlier. Although surgical patients tend to have a stormier clinical course related to CDI, overall they do better than medical patients. Future studies focusing on modifiable risk factors for each group are needed.